Renunciation of the self in psychotherapy - Welsh, Robert (Mental health, religion & culture, 2009)
Self-renunciation or self-denial, although often misunderstood, is a foundational concept in several major religions and is frequently associated with spiritual maturity. In spite of this, the action of self-renunciation has been viewed with suspicion by the psychological community and criticized as repressive. This article argues that the concept of self-denial found in the Sufi tradition of rebirth and the salvation paradox found in the synoptic Gospels can bring a valuable perspective to psychotherapy. First, a brief summary of the history of psychotherapy and its contributions to the understanding of the self are provided. Next, a cursory overview of the Sufi tradition of rebirth is given. Third, the salvation paradox found in the synoptic Gospels is reviewed. It is argued that these two traditions offer valuable insight into ideas surrounding the self. Finally, the clinical implications of self-denial are discussed, and conclusions are drawn related to how psychotherapy can benefit self-renunciation.